PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI "GEMPUR HIPERTENSI DENGAN CERDIK" DI PUSKESMAS GEDEG - Claudia Key; Sukma Sahadewa; Atik Sri Wulandari; I Made Krisna Naradha; Triesta Mystah Istyadzah; Prada Marwah Al Kamilah; Reza Hesty Viona; Putu Ayu Aryanda Parawidnyaningsih; M.Raffli Naresca Pradana; Ni Kadek Niken Ayu Lestari; Gere Yusuf Kelly; Ayu Cahyani Noviana (Jurnal Riset Multidisiplin Edukasi, 2026)
Hypertension is a crucial global health challenge often referred to as the silent killer due to the absence of obvious early clinical symptoms and the low level of patient awareness regarding their condition. This condition necessitates strong preventive measures at the grassroots level through massive and continuous health education. This community service activity aims to improve public health status through in-depth education on the dangers of hypertension and to build a commitment to lifestyle changes through the CERDIK behavior guidelines. The activity was conducted in the polyclinic waiting room of the Gedeg Community Health Center (Puskesmas Gedeg) from February 20 to 21, 2026, involving a target audience of 40 adult and elderly patients. The implementation approach focused on health promotion and prevention through interactive two-way lectures, which were reinforced by visual stimuli using leaflets. The program's achievement and success levels were evaluated using pre-test and post-test questionnaire instruments. The results showed a predominance of female participants (60%), with a diverse age range between 20 and 82 years. There was a significant increase in the participants' average score, rising from 70.25 before the intervention to 91.75 after the health education. Evaluation calculations indicated a 30.6% increase in knowledge and material absorption. In the post-test results, all participants (100%) successfully reached the "Good" knowledge category, shifting drastically from the pre-test results where the majority were still in the "Sufficient" category (45%). In conclusion, this educational activity effectively and tangibly improved participants understanding of the definition of hypertension, its risk factors, complication prevention, and the application of the CERDIK lifestyle.